Analisis Rantai Nilai Pendidikan Kejuruan dalam Mengembangkan Entrepreneurship : Studi Kasus pada SMK PGRI 20 Jakarta - Nur Kholis; Basuki Wibawa; Soeprijanto Soeprijanto (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2019)
This study aims to identify value chain models in vocational education in developing entrepreneurship. The research method used in this study uses a qualitative approach. The results of the performance of value chain activities that provide added value in developing entrepreneurship are operating activities and marketing activities. Operational activities include curriculum development activities, teaching and learning activities, student self-development and assessment standards. While marketing activities include professional certification institutions and school collaboration with DUDI. There are several activities that can improve the performance of the value chain in developing entrepreneurship, including: (1) Joint commitment to internalize the values of entrepreneurship in each learning activity. (2) Making the development of entrepreneurial learning models based on Contextual Teaching Learning. (3) Optimizing and developing entrepreneurial classes that have been carried out on a massive scale to evaluation and follow-up. (4) Testing of professional certification is carried out in stages with the unit competency scheme. (5) Making production units based on expertise competencies and other relevant competencies. (6) Developing teaching factories both in schools and other institutions that can become facilities for students improve their competence. (7) Creating a small business assistance program for students and graduates through a project work business. (8) Open a new network of cooperation with government agencies or private institutions that focus on the creation of small businesses for students and graduates.